The Relationship Between School Administrators' Social Justice Leadership Behaviors and Teachers' Levels of Organizational Happiness - Sebila, Bulbul; Cemaloglu, Necati (Technium Social Sciences Journal, 2025)
The purpose of this study is to examine the relationship between school administrators' social justice leadership behaviors and teachers' levels of organizational happiness, according to the perspectives of teachers. The study adopts a relational survey model and employs a quantitative research approach. The population comprises 4000 teachers from primary and secondary schools in a Turkish province for the 2024 -2025 academic year, with a sample of 380 teachers selected via purposive sampling. Data collection tools include a Personal Information Form, School Principals' Social Justice Leadership Behaviors Scale, and Organizational Happiness Scale. Data analysis was performed using SPSS 25. Descriptive statistics, including arithmetic mean and standard deviation, were calculated to address the first two sub-problems. Correlation analysis was used to address the third sub-problem, and multiple regression analysis was performed to examine the fourth sub-problem. The findings indicate that social justice leadership behaviors of school administrators are perceived as moderately high, with "Support" emerging as the most prominent sub-dimension. Teachers' organizational happiness levels are also perceived as moderate to high, with "Realization of Potential" being the highest- rated sub-dimension. Correlation analysis reveals a significant positive relationship between social justice leadership and organizational happiness, with supportive leadership behaviors strongly associated with positive emotions and fulfillment. Conversely, leadership behaviors that lack participatory and reflective elements show weaker predictive power regarding organizational happiness. The regression analysis underscores that "Support" is the most significant predictor of teachers' organizational happiness, highlighting the critical role of supportive leadership in fostering a positive organizational environment. The study concludes by emphasizing the importance of inclusive, equitable, and support-based leadership practices to enhance teachers' well-being and professional satisfaction.